Pengembangan Model Gas Conditioning Unit dalam Sistem Seal Gas di Kompresor Sentrifugal: Studi Kasus Kerusakan Dry Gas Seal - Riswan Adhitya Saputra (Institut Teknologi Sains Bandung, 2021)
Dry gas seal is an important component in the sealing system in centrifugal compressors. The gas seal supply that enters the dry gas seal must meet the specifications that have been determined based on API 692. However, on reality at the site dry gas seal damage often occurs, one of which is due to contamination from the gas seal supply that will enter the dry gas seal. The sulfur contamination in the corrosive process gas reduces the life and reliability of the dry gas seal. In addition, the selection of a gas conditioning unit model that is not quite right will result in the gas seal supply quality beyond the predetermined specifications. In this study, to obtain a good quality gas seal supply, development was carried out in the existing gas conditioning unit, upgrade seal gas strainer design using the duplex type and changing the type of strainer, changing the size of the gas filter seal from 0.3 micron to 0.1 micron and the use of coalescing. filter, repair seal gas heater and heat tracing installation on the seal gas piping, and finally replacement of seal gas booster components. The research method used is the study of literature from various references and previous studies, collecting data in the field and analyzing the findings using the PROACT method. From the analysis, it can be concluded that the development of the gas conditioning unit model in the gas seal system has a positive impact on the reliability of the dry gas seal in this centrifugal compressor.